Ortensia De Meo and the Neapolitan socialist women’s movement (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
The paper constitutes a contribution to the research strand on women’s political militancy. In the context of the “new biography” approach, it analyses the political and private experiences of Ortensia De Meo and the group of activists who, alongside her, established the first socialist women’s organisation in the southern Italian city of Naples. The group is composed of Ortensia De Meo, Ida and Ines Garbarini, Adele Barbarossa, and sisters Enrichetta and Stella Giannelli. It represents a minority but tenacious group of militants from diverse generations, backgrounds, and social origins, unified by a profound sense of solidarity and a shared commitment to advancing a comprehensive movement for social change.
Keywords: Women’s Political Activism; Biographies; Socialism; Mezzogiorno